ORGANIZATIONAL CULTURE AS CRITICAL SUCCESS FACTOR IN THE IMPLEMENTATION OF KNOWLEDGE MANAGEMENT IN ORGANIZATIONS - Bissoli dos Santos, Vanessa Cristina [UNESP]; Martins Damian, Ieda Pelogia [UNESP]; Pomim Valentim, Marta Ligia [UNESP] (Univ Federal Campina Grande, 2019)
Currently, knowledge management has been gaining ground and has been understood as a management model that contributes to the survival and development of different types of organizations in an increasingly complex and dynamic environment. Knowledge is considered one of the strategic organizational resources and, at the same time, a foundation and subsidy for the creation of competitive differentials. In this context, several critical success factors can impact the implementation of a knowledge management model, such as organizational culture. Culture can influence learning, behavior, and sharing of organizational knowledge. In this perspective, this text aims to demonstrate the importance of understanding the organizational culture as a critical success factor, evidencing the impacts in the implementation of knowledge management in organizational environments.
Keywords: Knowledge Management; Critical Success Factors; Organizational Culture; Informational Culture